SNR measurement in a beamforming network - Abdul Rahim, Sharul Kamal; Gardner, Peter (JOHN WILEY & SONS INC, 111 RIVER ST, HOBOKEN, NJ 07030 USA, 2007)
Array antennas with integrated low noise amplifiers have been combined with a butler matrix (BM) to form a beamforming network that can improve the performance of wireless communication systems. The performance of a four-element array with and without the low noise amplifiers and with and without the BM have been evaluated, in terms of the measured signal to noise ratio (SNR) at each output port. These SNR output signals are then combined to calculate and compare the diversity gains available with selection combining and maximal ratio combining. The results show that selecting the strongest output from the BM gives SNR performance comparable with that of maximal ratio combining, when LNAs are used to compensate for the BM loss.